Alternativas al desarrollo y otras legalidades: el caso de Ecuador - Yesica Álvarez-Lugo (Revista Iberoamericana de Estudios de Desarrollo)
The emergence of post-development has been a turning point in the Development Studies. However, the bibliographic corpus that gives shape to this current of thought suffers from a scarce integration of legal questions in the critical analysis of developmental discourse, limited to references to legal pluralism. In this sense, it seems appropriate to highlight the importance of deepening the study of the relationships between alternatives to development and the legal field, as well as to draw attention to the need to qualify which type of legal pluralism is defended by post-development. Finally, we will present the Nature rights recognized in the 2008 Constitution of Ecuador as an opportunity to advance towards another Law that supports alternatives to development.